The hour [videorecording (DVD)] - Morgan, Abi; Morgan, Abi; Giedroyc, Coky; Bradbeer, Harry; Payne, Jamie; West, Dominic, 1969-; Garai, Romola, 1982-; Whishaw, Ben, 1980-; Chancellor, Anna; Chaplin, Oona, 1986- (Distributed by BBC Worldwide Americas : Distributed by Warner Home Video, 2011)
"London, 1956. At Lime Grove Studios, the BBC has just launched 'The Hour,' a topical news program. At the heart of the show are three contrasting journalists: enigmatic producer Bel Rowley, a spirited woman in a man's world; her best friend, Freddie Lyon, a brilliant and passionate reporter; and charming, well-connected front man Hector Madden. As Freddie moves to cover a significant but controversial story, the trio becomes entangled in an intense interplay of politics, ambition and romance, all ignited by a mysterious murder and chilling conspiracy." -- Container.